PENGARUH FAKTOR EKSTERNAL DAN INTERNAL TERHADAP INFEKSI HIV/AIDS PADA REMAJA DI WILAYAH KERJA PUSKESMAS DUNGINGI KOTA GORONTALO - Fadli Syamsuddin; Rahmat Kadir (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
This research was conducted at working area of Social Health Center Dungingi at Gorontalo City. The aimed of this research is to know the effecting of external and internal factor toward HIV/AID on toddlers in working area of Social Health Center Dungingi at Gorontalo City. This research is done with used descriptive analytic method, with design of research cross sectional study. The result showed the toddlers in working area of Social Helath Center Dungingi not getting the effect from the friends in the same age, that is many as 88,7%, not effecting by social media that is as many as 89,7%. The knowledge about HIV/AID infection in positive category, that is as many as 100%. Toddlers in working area of Social Health Center Dungingi the not effect by HIV/AID virus.